2019
DOI: 10.1371/journal.pntd.0007745
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis virus inhibits rRNA synthesis and host protein production in human cells of neural origin

Abstract: Tick-borne encephalitis virus (TBEV), a member of the genus Flavivirus (Flaviviridae), is a causative agent of a severe neuroinfection. Recently, several flaviviruses have been shown to interact with host protein synthesis. In order to determine whether TBEV interacts with this host process in its natural target cells, we analysed de novo protein synthesis in a human cell line derived from cerebellar medulloblastoma (DAOY HTB-186). We observed a significant decrease in the rate of host protein synthesis, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…We next aimed to compare the phenotypic characteristics of the rescued TBEV-Eu strain Salland to two well-characterized TBEV-Eu strains of known pathogenicity. For this, the TBEV-Eu reference strain Neudoerfl, which was isolated from ticks in 1971 and shows low to medium pathogenic potential 33 , was acquired through the European Virus Archive, whereas Hypr, a TBEV-Eu strain originally isolated from the blood of a deceased child in 1953 and which is considered highly virulent 29 , 33 35 , was acquired using Infectious Subgenomic Amplicons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next aimed to compare the phenotypic characteristics of the rescued TBEV-Eu strain Salland to two well-characterized TBEV-Eu strains of known pathogenicity. For this, the TBEV-Eu reference strain Neudoerfl, which was isolated from ticks in 1971 and shows low to medium pathogenic potential 33 , was acquired through the European Virus Archive, whereas Hypr, a TBEV-Eu strain originally isolated from the blood of a deceased child in 1953 and which is considered highly virulent 29 , 33 35 , was acquired using Infectious Subgenomic Amplicons.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, caution needs to be taken when extrapolating in vitro data to the situation in vivo. Yet, multiple studies have previously shown that TBEV replication efficiency in vitro is often associated with pathogenicity in vivo 29 , 30 , 33 , 35 , 47 , 48 , with highly pathogenic strains replicating faster and to higher titers than mildly pathogenic strains in a multitude of cell lines 29 , 30 , 35 , 47 , 48 and human whole blood samples infected ex vivo 49 . Nonetheless, reports in which TBEV growth kinetics in vitro do not directly correlate with pathogenicity in vivo are also known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed accelerated degradation of ubiquitinated proteins was probably due to the suppression of de novo protein synthesis ( Figure 7 (e)). Recently, it has been reported that suppression of host de novo protein synthesis is a hallmark of flavivirus infection [ 46 , 52 , 53 ]. We propose that it might be a common strategy for flaviviruses to suppress host de novo protein synthesis to accelerate proteasomal degradation of short-lived antiviral proteins to antagonize IFN signalling, as YFV similarly suppressed host de novo protein synthesis (Supplementary Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification was determined based on the ratio of total fluorescent intensity of IL‐1β relative to the nuclei (DAPI stain). Analyses were performed using ImageJ software (NIH, USA) (Selinger et al., 2019) to determine the pro‐ and mature IL‐1β levels.…”
Section: Methodsmentioning
confidence: 99%